Non-viral systems for intracellular delivery of genome editing tools - I. H. Shaikhutdinov; P. V. Ilyasov; O. V. Gribkova; L. V. Limareva (Вавиловский журнал генетики и селекции)
A hallmark of the last decades is an extensive development of genome editing systems and technologies propelling genetic engineering to the next level. Specific and efficient delivery of genome editing tools to target cells is one of the key elements of such technologies. Conventional vectors are not always suitable for this purpose due to a limited cargo volume, risks related to cancer and immune reactions, toxicity, a need for high-purity viral material and quality control, as well as a possibility of integration of the virus into the host genome leading to overexpression of the vector components and safety problems. Therefore, the search for novel approaches to delivering proteins and nucleic acids into cells is a relevant priority. This work reviews abiotic vectors and systems for delivering genome editing tools into target cells, including liposomes and solid lipid particles, other membrane-based vesicles, cell-penetrating peptides, micelles, dendrimers, carbon nanotubes, inorganic, polymer, metal and other nanoparticles. It considers advantages, drawbacks and preferred applications of such systems as well as suitability thereof for the delivery of genome editing systems. A particular emphasis is placed on metal-organic frameworks (MOFs) and their potential in the targeted intracellular delivery of proteins and polynucleotides. It has been concluded that further development of MOF-based vectors and technologies, as well as combining MOFs with other carriers can result in safe and efficient delivery systems, which would be able to circulate in the body for a long time while recognizing target cells and ensuring cell-specific delivery and release of intact cargoes and, thereby, improving the genome editing outcome.